The Right to Protest in Indonesia: Legal Boundaries and Democratic Dilemmas (Contemporary Issues on Indonesian Human Rights Law and Policy, 2024)
This paper explores the legal boundaries surrounding the right to protest in Indonesia, analyzing the evolving nature of public demonstrations in a post-Reformasi society. While Indonesia's Constitution guarantees the right to assemble peacefully, various legal and regulatory challenges have emerged in the context of political protests and social movements. This study investigates the balance between maintaining public order and respecting democratic freedoms, focusing on the role of the police, government regulations, and judicial interpretations in limiting or facilitating protests. Particular attention is given to controversial laws such as the 2018 omnibus law and the 2008 Law on Mass Organizations, which have been used to curtail protest activities. The research also examines the rise of online activism and digital protests, alongside traditional street demonstrations, and assesses the government's response to these new forms of political expression. By analyzing case studies from the Jakarta protests against labor reforms and the #MeToo movement, this paper discusses the democratic dilemmas that arise when the government seeks to regulate dissent. It concludes with recommendations for legal reforms to ensure that the right to protest is preserved without compromising national security or public order.